PENINGKATAN KOMPETENSI DAN MOTIVASI BELAJAR BAHASA INGGRIS MELALUI PENDEKATAN TERPADU (INTEGRATED APPROACH) BAGI MAHASISWA NON BAHASA INGGRIS - Samsul Amri (Wahana Pendidikan, 2022)
English as a subject in the higher education is used as supplement of the core courses. Dealing with the prelimenary observation, the learners do not yet use it maximally. It leads to lack of motivation, vocabulary, learning interest, time allocation, and others. Thus the reseacher chose the Integrated Approach to cope those problems. The study aims at investigating if the Integrated Approach boosts English proficiency and engagement in learning, as well as to see how learners’ progress and what variables affects their progress. it is designed as Classroom Action Research. Accounting major learners of the Islamic University of Indragiri were the respondents. Test results and questionnaires were utilized in gathering the data. Additionally, the research findings reveal that there are better results on the learners’ profeciency and motivation in leearning English. Some integrated processes support their improvement that comprise of civilizing, investigating, observing, controlling, and rehearsing. Moreover, internal and external variables including learner autonomy, instructional approaches, and educator tasks are influencing the advancement. Finally, the use of Integrated leads to better learners' academic achievement and engagement.